2018
DOI: 10.3390/molecules24010024
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Antioxidant Activity, and Biological Effects of European Cranberry (Vaccinium oxycoccos)

Abstract: Lesser known fruits or underutilized fruit species are recently of great research interest due to the presence of phytochemicals that manifest many biological effects. European cranberry, Vaccinium oxycoccos fruit, as an important representative of this group, is a valuable source of antioxidants and other biologically active substances, similar to American cranberry (V. macrocarpon) which is well known and studied. European cranberry fruit is rich especially in polyphenolic compounds anthocyanins (12.4–207.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 101 publications
1
75
1
1
Order By: Relevance
“…The major phenol in M. rhodantha and M. spinosissima was gentisic acid. Gentisic acid was discovered in a few species such as Momordica charantia leaves (12.75 mg g −1 ) [23] and Vaccinium oxyccocos fruit (0.3 mg 100 g −1 ) [24] and is rare in general. Gentisic acid is a strong anti-oxidant and has important health benefits [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The major phenol in M. rhodantha and M. spinosissima was gentisic acid. Gentisic acid was discovered in a few species such as Momordica charantia leaves (12.75 mg g −1 ) [23] and Vaccinium oxyccocos fruit (0.3 mg 100 g −1 ) [24] and is rare in general. Gentisic acid is a strong anti-oxidant and has important health benefits [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The conducted studies revealed differences between the varieties of snowball tree in the content of total sugars. Studies by Shchetilina et al (2016) 2010, Kucharska et al, (2015), Jurikova et al (2019) proved that a particularly important role of pectins is the prevention of many types of cancers. Pectin solutions have been shown to have antibacterial properties (Skrovankova et al, 2015;Ceylan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One of the important glycosides of snowball tree is iridoid viburnin. Česonienė et al (2010), Skrovankova et al (2015), Tsuchiya (2015), Jurikova et al (2019) demonstrated that in pharmacy on the basis of iridoids of natural origin, preparations of cardiovascular and antispasmodic group can be produced, and the results of recent studies (Stępień, et al, 2010;Kucharska et al, 2015;Skrovankova et al, 2015) have revealed its antitumour activity. Furthermore, (Kraujalytė et al, 2013;Kucharska et al, 2015;Konarska & Domaciuk, 2018;Jurikova et al, 2019) have confirmed that biologically active substances of V. opulus manifest hemostatic, antiseptic, tonic effect on the human body, and also increase the tone of the uterine muscles and prevent the appearance of varicose veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of antioxidants of natural origin (mainly PFCs), as CAS, in cosmetic products (products for skin protection from the OS, for skin care after sun exposure, for prevention and anti‐ageing products) is regarded as justified and is also present in actual dermatological practice and skin care. PFCs can be found in many plants, as well as in the investigated wild apple fruit . This PFCs (phenols, flavonoids, tannins and anthocyanins) may directly ‘scavenge’ free radicals caused by the OS, demonstrating a high affinity for the reactive oxygen species‐ROS, can inhibit the formation of new ROS, activate antioxidant enzymes, chelate prooxidant metal ions and neutralize free radicals.…”
Section: Introductionmentioning
confidence: 99%